Computation of Steady Free Convective Boundary Layer Viscous Fluid Flow and Heat Transfer towards the Moving Flat subjected to Suction/Injection Effects - Ferdows, Mohammad; Shamshuddin, Mohammed; Zaimi, Khairy (CFD Letters, 2021)
The steady free convective boundary layer viscous fluid flow and heat transfer towards the moving flat plate is investigated. It is important to study the fluid flow and heat transfer problems in the presence of suction and injection effects due to an extensive variety of applications in engineering and industry. Thus, the main objective of the present study is to analyse the impacts of the suction and injection parameter on the velocity and temperature of the fluid as well as the skin friction and the Nusselt number coefficients. The problem has coupled partial differential equations which are converted into ordinary differential equations by employing similarity transformation and adopting of the strong wall suction. The ordinary differential equations thus obtain are handled numerically by utilizing Maple software simulation. The main findings concerning the behaviours of velocity and temperature against various values of the emerging physical parameter such as suction/injection are presented clearly in this numerical examination via graphical illustrations whose physical explanation are discussed thoroughly based on a strong theoretical basis. Furthermore, skin friction and Nusselt number results are studied at different values of pressure gradient. The detail geometry reveals that the velocity and temperature of the fluid decreases with increase of suction/injection parameter. Both skin friction coefficient and Nusselt number decreases with an increase of suction/injection parameter.